Characterization of CD34+ hematopoietic progenitor cells in JAK2V617F and CALR-mutated myeloproliferative neoplasms. (September 2016) - Angona, Anna; Alvarez-Larrán, Alberto; Bellosillo, Beatriz; Longarón, Raquel; Camacho, Laura; Fernández-Rodríguez, M. Concepción; Pairet, Silvia; Besses, Carles
Highlights: CALR -mutated ET patients harbored a higher mutant load at progenitor level than JAK2 -positive ET. Hematopoietic stem cells of CALR -mutated ET showed a similar mutational load than CALR- mutated MF. The mutated clone size in chronic phase of MPN is different according to genotype. Abstract: Mutations in JAK2 or CALR are observed in patients with myeloproliferative neoplasms (MPN). To get further insight in the dynamics of the mutant clone, we assessed the mutant allele burden in hematopoietic stem cells (HSCs), hematopoietic progenitor cells (HPCs) and granulocytes from 138 patients [51 polycythemia vera (PV), 58 essential thrombocythemia (ET) and 29 myelofibrosis (MF)]. CALR -mutated ET patients harbored a higher mutant load at progenitor level than JAK2 V617F-positive ET (HSCs: 39.9% vs 7.5% p < 0.001, HPCs: 32.7% vs 7.7% p < 0.001). Moreover, HSCs of CALR -mutated ET patients showed a similar mutational load than patients with CALR- mutated MF (39.9% vs 48.2%, p = 0.17). Regarding JAK2 V617F MPN, PV and ET patients showed a low mutational burden at progenitor level whereas in the myelofibrotic phase the dominance of the mutated clone was a constant finding. In conclusion, the size of the mutated clone in chronic phase MPN is different according to genotype with CALR -mutated ET showing a pattern similar to that observed in MF.